MEMAHAMI MANAJEMEN RISIKO SERTA LANDASAN HUKUM DALAM AGAMA - Uswatun Hasanah; Jamilatul Mahya (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2023)
In this article, the author intends to explain a little about learning about risk management. Also to get maximum and sustainable benefits in risk management. Which is the implementation of several management functions in risk management, especially the risks faced by an organization/company. Therefore, risk management can be said as a comprehensive set of policies and procedures that an organization has to manage, monitor and control risks that may arise. So that it can find good specifications in potential losses, evaluate potential losses, and choose the right technique/way to determine a combination in achieving the goals of an organization/company. In order to also be able to know the legal basis of risk management in overcoming an organization/company. Islam views risk as suffering, which is undesirable for its own sake. Suffering is desirable only when it contains benefits that outweigh the costs associated with suffering, or in other words, risk is desirable only when it can be a stimulus to productive endeavors and activities that add value. Islam also links risk with luck. So, if luck is associated with obtaining sustenance, then there are ten keys to unlocking sustenance according to the Qur'an and Al-Sunnah that should be lived and believed so that a person gets good luck and obtains sustenance that is lawful and good and blessed, as Allah says.